Benchmarking SARS CoV-2 Infection in the Workplace to Support Continuity of Operations. Issue 7 (July 2021) - Iddins, Bart O.; Waugh, Mark H.; Buck, Brandon; Cato, Tracey; Graham, David E.; Attia, Kareem; Jones, Dan; Partin, Adam; Shourbaji, Rania; Wesh, Christopher
Abstract : Objective: The COVID-19 pandemic jeopardizes continuity of operations of workplaces and the health and safety of workers. Exemplar workplace-related SARS-CoV-2 benchmarks are described and illustrated with empirical data. Methods: Benchmarks were collected over a 9-month period on a large workplace ( N = 5500+). These ranged from quantitative indices associated with RT-qPCR targeted testing and random surveillance screening, surveillance for new variants of SARS-CoV-2, intensive contact tracing, case management, return to work procedures, to monitoring of antibody seropositive status. Results: Data and analyses substantiated effectiveness of interventions. This was evidenced in suppressed infection rates, rapid case identification and isolation, acceptance of the program by employees, documentation of presumptive immunity, and working relationships with senior management. Conclusions: These SARS-CoV-2 exemplar benchmarks provided an evidence-base for practice and contributed strategically to organizational decisions. Abstract : Supplemental Digital Content is available in the text